Amidate Prodrugs of O-2-Alkylated Pyrimidine Acyclic Nucleosides Display Potent Anti-Herpesvirus Activity - Luo, Min (ACS Med Chem Lett, 2020)
[Image: see text] Three series of amidate prodrugs of O-2-alkylated acyclic nucleosides of the 3-fluoro-2-(phosphonomethoxy)propyl (FPMP), cyclic 3-hydroxy-2-(phosphonomethoxypropyl) (cHPMP), and 2-(phosphonomethoxypropyl) (PMP)-type featuring cytosine and 5-fluorocytosine as nucleobases were readily synthesized. Both the aspartic acid ester and valine ester prodrugs of (R)-O-2-alkylated FPMPC exhibited potent anti-HCMV and VZV activity in the micromolar range. In addition, the valine ester prodrugs of 5-fluorocytosine (R)-O-2-alkylated FPMP and (R)-O-2-alkylated cHPMPC showed inhibitory activity at molar concentrations against these viruses.